2000
DOI: 10.1152/ajpregu.2000.279.6.r1996
|View full text |Cite
|
Sign up to set email alerts
|

Na+/H+exchange in mosquito Malpighian tubules

Abstract: Fluid secretion and intracellular pH were measured in isolated mosquito Malpighian tubules to determine the presence of Na(+)/H(+) exchange. Rates of fluid secretion by individual Malpighian tubules in vitro were inhibited by 78% of control in the presence of 100 microM 5-(N-ethyl-n-isopropyl)-amiloride (EIPA), a specific inhibitor of Na(+)/H(+) exchange. Steady-state intracellular pH was measured microfluorometrically by using 2', 7'-bis(2-carboxyethyl)-5(6)-carboxyfluorescein in individual Malpighian tubules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…Distinct segments of the tubule exhibit apical, intracellular and both basal and apical localization patterns for NHE3. This is consistent with Petzel's suggestion that the basolateral Na + /H + exchange resembles the pharmacology of vertebrate NHE3 (Petzel, 2000). However, differential localization patterns might indicate its functional diversity at specific segments of the tubule.…”
Section: Sequence and Phylogenetic Relationship Of Invertebrate Nhessupporting
confidence: 90%
See 1 more Smart Citation
“…Distinct segments of the tubule exhibit apical, intracellular and both basal and apical localization patterns for NHE3. This is consistent with Petzel's suggestion that the basolateral Na + /H + exchange resembles the pharmacology of vertebrate NHE3 (Petzel, 2000). However, differential localization patterns might indicate its functional diversity at specific segments of the tubule.…”
Section: Sequence and Phylogenetic Relationship Of Invertebrate Nhessupporting
confidence: 90%
“…However, D. melanogaster Malpighian tubules were shown not to express any known Na + channels (Giannakou and Dow, 2001). The amiloride derivative EIPA, which is more potent towards NHEs, does indeed affect tubular pH and recovery from acid load, lending support to the involvement of NHE-like molecules in apical membrane transport (Petzel, 2000).…”
Section: Sodium/proton Exchangers (Nhes)mentioning
confidence: 76%
“…Similar reciprocal changes in intracellular K + and Na + concentrations in the presence of bumetanide in Malpighian tubules of Aedes aegypti would be expected to lead to the observed decrease in the K + concentration and the increase in the Na + concentration in secreted fluid (Fig.·2). Even though bumetanide blocks the entry of both K + and Na + into the cell, the intracellular Na + can still rise because three other pathways for Na entry remain open: (1) Na + /H + exchange transport (Hegarty et al, 1992;Petzel, 2000), (2) an Na + conductance that accounts for 16% of the total conductance of the basolateral membrane (Beyenbach and Masia, 2002) and (3) K + channels that apparently allow the passage of some Na + (Fig.·3). Of these three, Na + entry via Na + /H + exchange is probably the most important pathway because amiloride, a blocker of Na + /H + exchange, inhibits transepithelial Na + secretion by 70% (Hegarty et al, 1992).…”
Section: Stimulation Of Transepithelial Na + Secretion By Bumetanidementioning
confidence: 99%
“…However, no NHE 'isoform' has been molecularly characterized in any insect system, although some studies have suggested their existence in some insect tissues involved in ion transport (Giannakou and Dow, 2001;Hart et al, 2002;Pannabecker, 1995;Petzel, 2000) Given the importance of NHEs in regulating cellular and systemic pH, and ion transport and their potential to be functionally coupled to the activities of V-ATPases, molecular identification of members of this family is required in order to formulate a comprehensive model to understand how mosquitoes efficiently regulate ion and fluid balance following a blood meal. The cascades culminating in and initiated through these processes are crucial for the reproductive biology of mosquitoes and for disease transmission vectored by these insects.…”
Section: Introductionmentioning
confidence: 99%
“…Implicit in this model is that the K + (or Na + )/H + exchanger virtually operates in reverse to pump H + from the lumen in to the cell, which is a property exploited in vertebrate epithelial cells to clone NHE-deficient cell lines (Paris and Pouyssegur, 1983;Pouyssegur et al, 1984). The molecular identity of these Na + or K + /H + exchangers has been suggested from pharmacological studies on isolated Malpighian tubules (Petzel, 2000), or from the recently completed insect genome sequences (Adams et al, 2000;Holt et al, 2002;Pullikuth et al, 2003).…”
Section: Introductionmentioning
confidence: 99%